Metode Pembelajaran Inovatif Kurikulum Merdeka: Integrasinya Dengan Keterampilan Abad-21 - Hadiat, Hadiat (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
This study focuses on the basic concepts of using innovative learning methods from a typological perspective. In fact, innovative learning styles are conventional learning styles that have long been applied and developed in such a way and are associated with the Independent Curriculum concept which is largely oriented towards student activities in a centralized manner as a support for having skills in the 21st century which emphasizes the development of life skills. In this research, the method used is a qualitative study with a literature review approach. Based on the information obtained, research results were obtained in the form of understanding innovative learning methods, types of innovative learning methods, and; syntax of innovative learning methods. The urgency of this research is to obtain a comprehensive understanding regarding a particular topic while building a theoretical and practical foundation for further research.